A collecting trip to San José del Guaviare, Colombia, with the description of a new species of Perissolestes (Zygoptera: Perilestidae) - Florez, Tatiana (2023)
This study aims to preliminary assess the taxonomic diversity of dragonflies and damselflies from San José del Guaviare, Guaviare Department, Colombia. A total of 47 species were collected at five localities in different freshwater ecosystems during a field trip. We highlight three new species records for the country: Erythrodiplax tenuis Borror, 1942, Micrathyria spinifera Calvert, 1909, and Perithemis rubita Dunkle, 1982. Finally, a new species of Perissoletes is described from Guaviare and Casanare, Colombia.